WHO'S ARGUING? A CALL FOR REFLEXIVITY IN BIOETHICS - Ives, Jonathan (Bioethics, 2010)
In this paper we set forth what we believe to be a relatively controversial argument, claiming that ‘bioethics’ needs to undergo a fundamental change in the way it is practised. This change, we argue, requires philosophical bioethicists to adopt reflexive practices when applying their analyses in public forums, acknowledging openly that bioethics is an embedded socio-cultural practice, shaped by the ever-changing intuitions of individual philosophers, which cannot be viewed as a detached intellectual endeavour. This said, we argue that in order to manage the personal, social and cultural embeddedness of bioethics, philosophical bioethicists should openly acknowledge how their practices are constructed and should, in their writing, explicitly deal with issues of bias and conflict of interest, just as empirical scientists are required to do.